PEREMPUAN PROFESIONAL: RESISTENSI JURNALIS, GURU, DAN PEGAWAI TERHADAP BIAS GENDER DI TEMPAT KERJA - Ahmad Yasser Effendi (Jurnal Ilmiah Sosiologi Agama (JISA), 2026)
This article examines the experiences and forms of resistance among professional women facing gender bias in the workplace, focusing on three key professions: journalists, teachers, and public bureaucrats. Although these fields are commonly perceived as domains of professionalism, women within them continue to encounter subtle symbolic and structural barriers in the form of subtle gender bias. Employing a qualitative approach and in-depth interviews with nine female informants across the three professions, this study analyzes how resistance is constructed symbolically, narratively, and collectively. The findings reveal that professional women’s resistance often takes non-confrontational yet effective forms, such as role negotiation, solidarity alliances, and efforts to construct self-images as rational and competent actors. This article contributes to gender sociology discourse by highlighting the dynamics of bias that are not always explicit yet remain detrimental to women. It also underscores the necessity of gender-sensitive institutional reforms to ensure that professionalism no longer functions as a space for reproducing inequality.